Students' Perceptions of the Backwash Effect of Authentic Assessment in Recount Text Writing - Neni Afrida Sari Harahap; Dwi Nazwa Salsabilah Harahap (Invention: Journal Research and Education Studies, 2026)
This study aims to investigate three research problems: (1) students' perceptions of authentic assessment in personal experience recount text writing tasks, (2) the benefits of authentic assessment in recount text writing, and (3) the difficulties students encounter and the backwash effect of authentic assessment on their writing learning. Data were sourced from ten seventh-grade students at MTs Cerdas Murni Deli Serdang who had participated in authentic writing assessment activities. A descriptive qualitative research design was employed. Data were collected using a structured questionnaire consisting of 20 closed-ended items across three categories: students' perceptions, benefits of authentic assessment, and students' difficulties. Responses were analyzed using percentage-based descriptive statistics and interpreted qualitatively. Findings reveal that the majority of students hold positive perceptions of authentic assessment, with 90–100% expressing comfort, fairness, and clarity in the assessment process. All students (100%) agreed that writing about personal experiences aided idea expression and improved understanding of recount text structure. However, persistent difficulties were identified in vocabulary use (70%), past tense application (80%), organizing events (60%), and time management (100%). The study's implications suggest that authentic assessment not only serves as an evaluative instrument but also generates a positive backwash effect by fostering active participation, raising students' metacognitive awareness, and motivating continued writing practice. Teachers should integrate scaffolded writing support alongside authentic assessment to maximize its effectiveness in English language learning.